DIFFICULTY LEVELS IN THE MEASURES OF PHONOLOGICAL AWARENESS DISPLAYED IN THE PERFORMANCE OF CLASS SIX PUPILS WITH READING DISABILITIES IN SELECTED SCHOOLS IN NAIROBI COUNTY. - STEPHEN, DR. ORAGO O. (IJRDO - Journal of Social Science and Humanities Research, 2016)
The present study set out to establish the difficulty levels of the tasks used in measuring phonological awareness skills. In particular, it sought to determine the difficulty of the tasks using class six learners identified to be exhibiting reading difficulties from selected school in Nairobi County- Kenya. A sample of 25 pupils was engaged in the study after administering a reading disabilities diagnostic test. The tests were categorised as: Non-word Reading, Phoneme Blending, Phoneme manipulation, Phoneme Segmentation and Phoneme Production. The data were obtained from tape - recorded texts and marking of the scores of the respondents in the tests. The scores in the test displayed the levels of difficulties in the tasks. The results showed that phonological production was the least difficult with the most difficult being phoneme segmentation of the entire phonological awareness task.